Morphometric Analysis of Calcaneal Angles (Bohler’s and Gissane’s angle) in the North Indian Population (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Background: Calcaneal fractures are the most common tarsal bone injuries, accounting for 60–70% of tarsal fractures, and frequently occur due to high-energy trauma such as road traffic accidents and falls from height. These fractures significantly impair mobility and work capacity, particularly among individuals aged 21–45 years. Radiographic assessment using Bohler’s and Gissane’s angles is essential for determining fracture severity and guiding appropriate treatment planning.Methodology: A study was conducted in the SGT University Hospital Gurugram, Haryana. The study included 100 cases (60M, 40F), with mean age 41.66 ± 17.14 years (Range 15 - 89 years). Ankle lateral radiograph was taken by using CR X-ray machine (Fuji Modality). Lateral ankle radiographs in all the cases were evaluated for the measurement of Bohler’s and Gissane’s angle with the help of experienced Radiologist and Orthopedician.Result: The mean of Bohler’s angle and Gissane’s angle in the north Indian population were 28.70° (15 - 54°) and 112.18° (100 - 13°) respectively. The mean Bohler’s angle was found highest (30.57 ± 5.88°) in age group with age ranged from 15 - 29 years and lowest (27.44 ± 7.36°) in age group with age ranged from 30 - 44 years whereas Gissane’s angle was found highest (116.56 ± 10.03°) and lowest (109.77 ± 5.54°) in age group with age range of 75 - 89 years and 30 - 44 years respectively. There was no significant Difference in the Bohler’s and Gissane’s angle between males and females.Conclusion: In the north Indian population, the mean of Gissane’s angle and mean Bohler’s angle was found 28.70 ± 7.24° and 112.18 ± 7.09° respectively. There was no significant Difference in the Bohler’s and Gissane’s angle between genders.